Biodistribution of two octreotate analogs radiolabeled with indium and yttrium in rats - Laznickova, A; Laznicek, M; Trejtnar, F; Maecke, H R; Eisenwiener, K P; Reubi, J C (Anticancer research, 2010)
BACKGROUND: In this study, two octreotate derivatives N-[4-carboxy-4-[4,7,10-tris(carboxymethyl)-1,4,7,10-tetraazacyclododecane-1-yl]butanoyl]-Tyr(3)-octreotate (DOTAGA-tate) and N-[[4,10-bis(carboxymethyl)-7-(1(1,3-dicarboxypropyl))-1,4,7,10-tetraaza-cyclododec-1-yl]acetyl]-Tyr(3)-octreotate (DOTA-t-GA-tate) were radio-labeled with (111)In or (88)Y and their biodistribution profiles together with their elimination characteristics in rats were compared. MATERIALS AND METHODS: Radiolabeling of the peptides with high radiochemical purity was carried out in an acetate buffer with gentisic acid as radioprotective compound. Biodistribution profiles of the radiolabeled peptides were determined in intact male Wistar rats after an intravenous dose of 1 microg/kg. For elimination pathways analysis, studies in intact rats in metabolic cages and perfused rat kidney and liver were carried out. RESULTS: Fast radioactivity clearance from rat tissues (excepting somatostatin receptor-rich organs and the kidney) was determined for all agents under study. Profound radioactivity uptake in organs with a high density of somatostatin receptors (namely the adrenals and pancreas as biomarkers of somatostatin receptor-positive tissue) was slightly higher for radiolabeled DOTAGA-tate when compared with DOTA-t-GA-tate. Significantly higher accumulation in kidney and somewhat lower urinary elimination of (111)In-labeled peptides in comparison with that of (88)Y-agents were determined. Perfused rat kidney experiments confirmed that glomerular filtration was the main elimination mechanism for the compounds under study; their bile clearances in the perfused rat liver were negligible. CONCLUSION: (111)In((88)Y)-DOTAGA-tates exhibited higher distribution into somatostatin receptor-rich organs when compared with the corresponding radiolabeled DOTA-t-GA-tates. Higher uptake of (111)In-labeled peptides in the kidney is attributed to its different coordination properties.
Keywords: ledviny; radioizotopy ytria; tkáňová distribuce; Kidney; krysa rodu Rattus; Indium Radioisotopes; oktreotid; zvířata; potkani Wistar; Octreotide; Rats, Wistar; Male; radioizotopy india; Yttrium Radioisotopes; Rats; Animals; mužské pohlaví; radiofarmaka; Tissue Distribution; Radiopharmaceuticals